Cephalometric Norms of Czech Population Sample - A. Řeháček; M. Janega; P. Hofmanová; P. Michalík; T. Dostálová (Czech Dental Chamber, 2011)
Objective: Term standard cephalometric values mean average value of cephalometric measurements which includes standard deviation. This is not an absolute number but the range of values, which were obtained by measuring the defined sample of the population. Material and Methods: The sample of the population in our study group was selected from patients of Charles University, 2nd Medical Faculty, and Department of Orthodontics. Selection criteria were: Class I occlusion, balanced facial profile, no previous orthodontic treatment, absence of denture, including dental implants. From the homogeneity point of view the probands were born in Czech Republic and belong to Caucasian population. 91 patients were evaluated (age range was from 18 to 45 years; 21 men and 70 women) in computer program - Dolphin imaging using McLaughlin cephalometric analysis. Results: The results showed that our patients are in Class I but position of lower frontal teeth is similar to compensatory mechanisms of Class II patients.